2012
DOI: 10.1108/17561391211242744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurial orientation on business performance

Abstract: Purpose -Focusing on the corporate entrepreneurship in China's emerging economy, the purpose of this paper is to explore the impact of network capabilities on entrepreneurial orientation and business performance. Design/methodology/approach -Questionnaires and statistical analysis are applied in this research. Findings -Based on the survey of small to medium-sized enterprises (SMEs) in the north-east of China, it is found that entrepreneurial orientation (EO) has a positive effect on business performance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
70
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 30 publications
(63 reference statements)
18
70
1
11
Order By: Relevance
“…As predicted, the results of the structural model revealed that entrepreneurial orientation and organizational were positively and significantly related. This finding is consistent with the findings of previous studies that examined the relationship between entrepreneurial orientation and organizational performance (Mahmood & Wahid, 2012;Sharma & Dave, 2011;Zhang & Zhang, 2012). It means that the higher the entrepreneurial orientation, the greater the organizational performance.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…As predicted, the results of the structural model revealed that entrepreneurial orientation and organizational were positively and significantly related. This finding is consistent with the findings of previous studies that examined the relationship between entrepreneurial orientation and organizational performance (Mahmood & Wahid, 2012;Sharma & Dave, 2011;Zhang & Zhang, 2012). It means that the higher the entrepreneurial orientation, the greater the organizational performance.…”
supporting
confidence: 92%
“…Contrary to the proposition that entrepreneurial activities within existing organizations contribute to improved organizational performance, extant empirical findings show that the relationship between entrepreneurial orientation and organizational performance is unclear and inconclusive (Rauch, Wiklund, Lumpkin, & Frese, 2009). Some researchers confirmed a positive relationship between entrepreneurial orientation and organizational performance (Arief, Thoyib, Sudiro, & Rohman, 2013;Jia, Wang, Zhao, & Yu, 2014;Karacaoglu, Bayrakdaroglu, & San, 2012;Mahmood & Wahid, 2012;Mokaya, 2012;Sharma & Dave, 2011;Zhang & Zhang, 2012). Others found a negative entrepreneurial orientation-performance relationship (Covin, Slevin, & Schultz, 1994;George, Wood JR, & Khan, 2001;Shamsuddin, Othman, & Shahadan, 2012;Slater & Narver, 2000).…”
mentioning
confidence: 99%
“…Recent literature found that social capital has a positive impact on the relationship between proactiveness, risk-taking and firm performance (e.g., Anderson & Eshima, 2011;Zhang & Zhang, 2012). Bridging ties refers to the extent to which a firm establishes bonds outside of the central industry network, typically with organizations from other fields (Geletkanycz & Hambrick, 1997).…”
Section: Interaction Effect Of Bridging Tiesmentioning
confidence: 99%
“…Proactiveness entails a forward-looking view that described by the introducing new products and services ahead of the competition and detecting future demand (Martin & Javalgi, 2015). Moreover, several studies have confirmed that EO is one of the significant resources does positively influence firm performance (Eggers et al, 2013;Dada & Watson, 2013;Zhang & Zhang, 2012;Anderson & Eshima, 2013;Kantur, 2016). In contrast, some studies found that there is no significant relationship between EO and firm performance (Chandrakumara et al, 2011;Affendy et al, 2015).…”
Section: Entrepreneurial Orientationmentioning
confidence: 96%